Tourism Initiatives and Their Impact on Sustainable Livelihoods in Chitlang Village - Jha, Rajesh Kumar; Gnyawali, Bishal; Sapkota, Kanhaiya (The Third Pole: Journal of Geography Education, 2025)
This study employs a Sustainable Livelihood Framework (SLF) to analyze how rural tourism initiatives in Chitlang, Nepal, generate employment and transform community livelihoods. Using a mixed-methods approach including geospatial analysis, semi-structured interviews (n=46), focus group discussions, and thematic analysis, we examine tourism’s impact across five livelihood capitals: financial, social, physical, and natural. Findings reveal that home stays, agro-tourism, cultural interpretation, and handicraft production diversify income streams, empower women and youth, and strengthen cultural preservation. However, challenges persist in seasonal employment, unequal benefit distribution, environmental strain, and cultural commodification. The study contributes novel insights by integrating community narratives with SLF to demonstrate how locally embedded tourism models foster economic resilience while highlighting governance gaps. We recommend inclusive policy frameworks, enhanced skill development, and ecological safeguards to optimize tourism’s role in sustainable rural development.